In Depth Analysis of the Home to Work Travel Pattern in the Istanbul Metropolitan Area - Elif Alkay (European Regional Science Association (ERSA), 2011)
This paper investigates home to work travel pattern in the Istanbul Metropolitan Area. Investigation explores commuting pattern in three steps. In the first step, the reasons for changing commuting time are explored initially in relationship to urban structure. Added explanation then considers the gender, tenure type, income, occupation and commuting type. The result related with gender is consistent with the previous studies however income is not. Occupation and commuting type appear to be strongly affected on differences on commuting time. In the second step, the home to work travel pattern is explored whether it reflects consistency with the standard urban economic theory. Results reflect that the behavioral assumption of cost minimization for the journey to work in the standard model is inadequate when explaining the relation between job and housing location. In the third step, the home to work travel pattern is investigated in local context in terms of spatial distribution of workers both on working and residential areas. While living and working at the same geographic part of the metropolitan area or the district decreases the commuting time, living and working at the different geographic part of the metropolitan area or the district significantly increases the commuting time.
Keywords: 330